The Pharmacological Activity Of Jamblang Plants Is Based On The Popularity Of The Solvent : Literature Review Article - Adinda Ayesha; Himyatul Hidayah; Gabriel Victory Makalalag; Muhammad Panji Wicaksono (Jurnal Ilmiah Wahana Pendidikan, 2023)
The jamblang plant is a plant that belongs to the Myrtaceae family. The parts of the jamblang plant that have pharmacological activity are fruit, roots, leaves, seeds, and stems where activity in these parts is often used as a medicinal plant. This study uses the literature review article (LRA) method, identifying, analyzing and interpreting all research results. The method used in this study is to use literature review articles (LRA), identify, analyze and interpret all research results. The results obtained from the research show that the jamblang plant (Syzygium cumini L.) has been shown to have various pharmacological activities, including as antibacterial, antifungal, antioxidant, antidiabetic, anticholesterol, and anti-inflammatory.